Primary mathematics and developing professional : multiple perspectives on attainment in numeracy - Millett,Alison; Brown, Margaret; Askew, Mike. (Springer : Springer, 2007)
A detailed account is given of the National Numeracy Strategy in England, a systemic government-imposed response to concern about standards implemented in 1999/2000. An earlier initiative sponsored by a United Kingdom charitable trust reacting to concern about primary numeracy was the Leverhulme Numeracy Research Programme.
Includes index.
Keywords: Mathematics -- Study and teaching (Primary) -- Great Britain; EDUCATION -- Teaching Methods & Materials -- Mathematics; Mathematics -- Study and teaching (Primary).